Distressed relationships: Lessons from the Norwegian banking crisis - Steven Ongena; David C. Smith; Dag Michalsen (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
This paper measures the economy-wide impact of bank distress on the loss of relationship benefits. We use the near-collapse of the Norwegian banking system during the period 1988 to 1991 to measure the impact of bank distress announcements on the stock prices of firms maintaining a relationship with a distressed bank. We find that although banks experience large and permanent downward revisions in their equity value during the event period, firms maintaining relationships with these banks face only small and temporary changes, on average, in stock price. In other words, the aggregate impact of bank distress on the real economy appears small. We analyze the cross-sectional variation in firm abnormal returns and find that firms that maintain international bank relationships suffer more upon announcement of bank distress.
urn:nbn:de:hebis:30-9671
Keywords: G21; C41; 330; bank relationship; bank distress; Norwegian banking crisis